Penerapan Tema Arsitektur Ekologi Pada Bangunan Agrowisata Padi Di Tabanan - I Made Panji Raditya Dikarasta; Agus Kurniawan; Made Anggita Wahyudi Linggasani (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
Agrotourism is a tourist attraction that utilizes natural business (agro) to become a tourist attraction. Of course to expand knowledge, experience, recreation, and business relations in the field of animal husbandry, livestock, fisheries. With so many agro-tourism sites offered in Indonesia, of course, this is a challenge for the managers of agro-tourism areas. One phenomenon in land use is land conversion (land conversion). This phenomenon is in line with the increasing need for and demand for land, both from the agricultural sector and from the non-agricultural sector due to population growth and development activities. Bali), one of which is the Wongaya Betan Subak, Mengesta Village, which is used as the center for food gateways for the Tabanan Regency. Mengesta Village is an agricultural area that has special characteristics because it has natural panoramas in the form of mountain ranges and beautiful stretches of terraced rice fields with an area of ​​around 4,437 hectares. Agricultural management is carried out in a poor traditional way with a touch of science and technology. The development of rice agro-tourism is carried out by adding tourism destinations that are in accordance with village potential. The addition of destinations includes restaurants that sell processed agricultural products, home stays as facilities to support tourists who want to stay overnight, education and practice from plowing fields to rice processing as well as education and practice regarding rice rehabilitation where there will also be interesting photo spots.